PERKEMBANGAN KEMAMPUAN MOTORIK KASAR MELALUI KEGIATAN TARI KREASI PADA ANAK USIA 5 - 6 TAHUN - Isep Djuanda; Nur Dwi Agustiani (Almarhalah, 2022)
ABSTRACTThis study aims to know gross motor skills development of children aged 5-6 years with creative dance activities and to determine the gross motor skills development of children aged 5-6 years can be increased by creative dance activities.The design of this study was classroom action research. The subjects were students of Al Amanah Islamic Kindergarten aged 5-6 years, with the object was gross motor skills development by creative dance activities. This study was conducted in pre-cycle, cycle 1 and cycle 2. Each cycle consists of planning, implementing, observing and reflecting. Data collection was obtained by observation, interview and documentation studies.The results showed: 1) Creative dance activities were able to develop gross motor skills of children aged 5-6 years at RA Al Amanah Depok which was shown by an increase in average results on all indicators: balance, agility and flexibility, with the results of 53.43% in the pre-cycle to 68.86% in cycle 1 and in cycle 2 by 88%; 2) Creative dance activities were able to develop gross motor skills of children aged 5-6 years at RA Al Amanah Depok. This is indicated by the results that have fulfilled the predetermined success criteria. Keywords: development, gross motor, creative dance